Integrated Marketing Communication in E-commerce (a Study Case of Customers Data Leakage in Tokopedia) - Namora Fitrianti Indah Marina; Sabrina Sofi Qadrifa (UMSU, 2022)
Tokopedia has faced an issue that had made customer trust lost due to cases of data being hacked and sold by irresponsible hackers. This issue is one of the biggest problems because it is widely circulated on one of the social media, namely Instagram. This research aims to find out the Integrated Marketing Communication (IMC) strategy implemented by Tokopedia related to the outstanding issues. In this study, the researcher uses a qualitative research approach and the type of design research is a case study. The data collection technique that used is journal articles, books, Tokopedia’s official website, news articles in various mass media or digital platforms such as Youtube and it is carried out from March 2020 to 2021. Data analysis is carried out by content analysis. The results of the study found that Tokopedia implemented an Integrated Marketing Communication strategy related to the issue of hacking user data to restore customer trust.